If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5y + -3) + -1(8y + 5) = 0 Reorder the terms: 4(-3 + 5y) + -1(8y + 5) = 0 (-3 * 4 + 5y * 4) + -1(8y + 5) = 0 (-12 + 20y) + -1(8y + 5) = 0 Reorder the terms: -12 + 20y + -1(5 + 8y) = 0 -12 + 20y + (5 * -1 + 8y * -1) = 0 -12 + 20y + (-5 + -8y) = 0 Reorder the terms: -12 + -5 + 20y + -8y = 0 Combine like terms: -12 + -5 = -17 -17 + 20y + -8y = 0 Combine like terms: 20y + -8y = 12y -17 + 12y = 0 Solving -17 + 12y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 12y = 0 + 17 Combine like terms: -17 + 17 = 0 0 + 12y = 0 + 17 12y = 0 + 17 Combine like terms: 0 + 17 = 17 12y = 17 Divide each side by '12'. y = 1.416666667 Simplifying y = 1.416666667
| 2x+5(6x-4)=44 | | 40(25+x)=1 | | 8x-14=3x-6 | | m+90=150 | | -16x^2+324=0 | | 9x+6=6x+4 | | 0=-15m^2+60 | | 8(4+x)=360 | | 10x+7=8x-6 | | 21-12=3(x-8) | | 2x-(x-1)=3+x | | .75x-16=2(x-3)+4 | | 8(4+x)=72.00 | | 6n-3+2n=-1 | | 20(4r-48)= | | 2x+3-2x=2x+7 | | 7(x+1)=6(x-3) | | 11x=7x+72 | | 3x+4(2x+1)=26 | | 12x^2-52x-9=0 | | -x^2+18x-45=0 | | 1783x-2x=37x-12 | | 2x-20i=8*4y | | 5h+7=19 | | 2x+7=x+29 | | c(2x-d)=4c | | 3-x+7=19 | | .4w-11=-3 | | 4(5r+45)= | | 2,236,000+(-17.740x)=3,500,000 | | a^2-3ax+2ap-6=0 | | 5(x-3)=2(x-5) |